DESARROLLO ANÁTOMO-HISTOLÓGICO DEL TESTÍCULO DEL NACIMIENTO A LA MADUREZ SEXUAL DE LA CODORNIZ (Coturnix coturnix) VARIEDAD JAPONESA - Rospigliosi Y., Juan de Dios (2003)
Anatomical, histological, and developmental testicular changes from birth to puberty were studied in 80 Japanese quails. Ten birds per week were body weighed and slaughtered to measure the testis. Testicular tissue samples were collected and evaluated. Body weight varied from 35 g at week 1 to 180 g at week 8. The length of the testis varied from 0.1 mm at week 1 to 8 mm at week 8. The presence of Leydig cells coincided with the appearance of secondary sexual characteristics at week 7. Spermatozoa in the seminiferous tubules were not observed, even by the end of week 8.